The Relationship between Weight and Age on the Decline in Functional Activities in State Civil Apparatus at the Cirebon City Environmental Service - Riswandani, Kahfi; Jafar, Muhammad Ali; Norlinta, Siti Nadhir Ollin (Symbiohealth, 2025)
The decline in functional activities is a health problem that is increasing globally, especially among workers of productive age, including the State Civil Apparatus (ASN). Internal factors such as age and weight are known to contribute to an increased risk of musculoskeletal disorders, including low back pain. This study aims to determine the relationship between weight and age to the decrease in functional activity in ASN at the Cirebon City Environmental Service. The study used a correlational analytical design with a cross sectional approach. The sample was taken by purposive sampling with a total of 51 respondents who met the inclusion criteria. Data was collected through a Google Form-based questionnaire that included biodata, Numeric Pain Rating Scale (NPRS), and Oswestry Disability Index (ODI). Data analysis was carried out using the Shapiro-Wilk normality test and the hypothesis test with parametric correlation analysis. The results showed that both age and weight were significantly related to decreased functional activity. Respondents with older age and above-normal weight have a higher prevalence of experiencing low back pain complaints in the moderate to severe category. It was concluded that the increase in age and body mass index contributed to an increased risk of decreased functional activity in ASN.